POETIC STUDIES IN THE LITERATURE OF MODERN UZBEK AND TURKISH WOMEN POETS (World Bulletin of Social Sciences, 2026)
This article examines the modern poetry of Uzbek and Turkish women poets, focusing on their formal innovations, thematic evolution, and artistic expression